ChemInform Abstract: Phase Transitions in the Ruddlesden—Popper Phase Li2CaTa2O7: X‐Ray and Neutron Powder Thermodiffraction, TEM, Raman, and SHG Experiments. Issue 20 (April 2016) - Galven, Cyrille; Mounier, Denis; Bouchevreau, Boris; Suard, Emmanuelle; Bulou, Alain; Crosnier‐Lopez, Marie‐Pierre; Le Berre, Francoise
Abstract: Li2 CaTa2 O7 is prepared by solid state reaction of stoichiometric amounts of CaCO3, Ta2 O5, and a 10% excess of Li2 CO3 (Al2 O3 crucible, 1150 °C, 28 h).